1982
DOI: 10.1182/blood.v60.3.595.595
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-macrophage-derived acidic isoferritins: normal feedback regulators of granulocyte-macrophage progenitor cells in vitro

Abstract: The recent identification of a leukemia-associated inhibitory activity (LIA) against granulocyte-macrophage progenitor cells (CFU-GM) as acidic isoferritins has now led to detection of this activity in normal bone marrow and blood cells. Detection of this activity depends on stimulation of CFU-GM by granulocyte-macrophage colony stimulatory factors (GM-CSF), and some conditioned media (CM) sources of GM-CSF (human placental and monocyte, mouse macrophage and WEHI-3) contained low levels of acidic isoferritin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…38 Macrophages activated by an aberrant inflammatory response are likely the main source of serum ferritin overproduction in AML patients. 16 However, it is not excluded that leukemic cells themselves could also contribute to serum ferritin elevation since a significant association was found between ferritin levels and leukocytosis (ie, tumor burden). Although our in vitro data are preliminary, it is plausible that AML cells could release ferritin in the extracellular media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Macrophages activated by an aberrant inflammatory response are likely the main source of serum ferritin overproduction in AML patients. 16 However, it is not excluded that leukemic cells themselves could also contribute to serum ferritin elevation since a significant association was found between ferritin levels and leukocytosis (ie, tumor burden). Although our in vitro data are preliminary, it is plausible that AML cells could release ferritin in the extracellular media.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cellular origin of ferritin is thought to reside in the mononuclear phagocyte system and hepatocytes, the precise source of serum ferritin in human hematological malignancies has yet to be determined. [16][17][18] We took advantage of publicly available transcriptomic databases to assess the expression of FTH1 and FTL in AML and normal HSC. Analysis of the bloodspot database and of the functionally defined leukemic stem cell (LSC)-specific signature showed that FTH1 and FTL were overexpressed in AML cells and LSC compared with normal HSC (Figure 3A-B).…”
Section: Expression Of Fth1 and Ftl Fth1 Gene Signature And Chemomentioning
confidence: 99%
“…For CFU-GM assays, cord blood cells were plated in 0.3 percent agar culture medium in the presence of 10 percent (vol/ vol) medium conditioned by the human cell line 5637 (5637CM, a source of colony-stimulating factors) as described elsewhere. 28 We counted colonies (>40 cells/aggregate) and clusters (3-40 cells/aggregate) containing granulocytes and/or macrophages after 14 days of incubation (5% C02, 5% 02, humidified conditions). We also plated cells to assay colonies deriving from CFU-GM, BFU-E, and CFU-GEMM in methylcellulose culture medium in the presence of 1 unit of erythropoietin (Toyoba New York, Inc., New York, NY) and 10 percent (vol/vol) 5637CM, as described elsewhere.29 Colonies forming in methylcellulose were also scored after 14 days of incubation under the same conditions as agar cultures.…”
Section: In Vitro Progenitor Cell Studiesmentioning
confidence: 99%
“…Although indirect in its action, EPO is produced by the kidney in inverse proportion to the oxygen tension developed there by the red cell mass. Lactoferrin and acidic isoferritins have been implicated as further feedback regulators of GM-CFC growth and development (Broxmeyer et al 1978(Broxmeyer et al , 1982. Elaborated by the mature granulocyte macrophage populations, they are reported to block the production of the appropriate colony-stimulating factors for GM-CFC development.…”
Section: Committed and Maturing Cellsmentioning
confidence: 99%